Material selection for raw gas pipeline at SBR#2 gas field - Riady, Rado; Soedarsono, Johny Wahyuadi; Riastuti, Rini; Adipurnama, Iman (Teknomekanik, 2022)
In engineering design, material selection is the process of choosing the best material for a specific process via a systematic material selection approach. This article described the material selection process for SBR#2 pipeline, which will be installed to flow raw gas from SBR#2 field to the nearest tie-in point. The material selection process starts with design requirement analysis to generate primary function and objectives, including its constraints, determine primary criteria to be evaluated, screen materials candidates based on criteria evaluation, and select the most suitable materials based on very specific requirements. The criteria were evaluated by performing value engineering with the performance criteria matrix tool. Materials selection, in this case, was determined by two main criteria: corrosion resistance and construction ability. Corrosion resistance was evaluated semi-quantitatively by applying NORSOK M-506 2005 spreadsheet, and construction ability were evaluated qualitatively based on field experience. Solid Corrosion Resistance Alloy (CRA)-Stainless Steel 316L pipe is the most suitable for this case.